Pengaruh Arus Kas Operasi terhadap Kemampulabaan Perusahaan : Studi Kasus pada PT. SMCB, Tbk dan PT. INTP, Tbk - Sutarti, Sutarti; Widarta, Edwin (Jurnal Ilmiah Ranggagading (JIR), 2010)
The purpose of this research is to recognize the influence and the relationship between the operating cash flow (X) and companyâs profitability (Y). The ratio which has been used for cash flow are the operating activities in terms of sales, which is the operating cash flow divided by sales whereas the profitability ratio is gross profit margin. Two cement companies (PT. Holcim Indonesia Tbk and PT. Indocement Tunggal Prakarsa Tbk.) which have been operated from 2004 until 2008 under the same industry was used for this research purpose. The analysis method used in this research is coefficient correlation analysis which is used to determine the relationship between variables; coefficient determination analysis is used to quantify a strong relationship between variables; and coefficient regression analysis is used to estimate the relationship between the dependent variable independent variable. Lastly, trend analysis is used to see an increase or a decrease (the flow) of each variable. The results of this research could be concluded that different outcomes from two cement companies have been recognized, which are (a) the format of operating cash flow statement from the SMCB case study showed a significant improvement of cash flow (79%), therefore, SMCB could optimize the operation of the operating cash flow statement by increasing the amount of net cash flow from operating activities for each period of time, whereas under INTP case, the net cash flow from operating activities have not showed a significant improvement (6%). (b) The relationship and the influence between operating cash flow statement and companyâs profitability and gross margin from SMCB case study, showed a significant result as the alpha equals 4.4% whereas INTP is alpha equals 15% with a significant relationship between variables (74.3%). The main factor of this insignificant result is the effect of the insignificant increase of the operating cash flow statement is not balance with the significant increase in sales. This is caused by the significant amount of cash receivable (non cash items) in INTP Company, that influences the result of the operating cash flow statement. Keywords : Operational cash flow and profitability